Convergence in Per Capita Energy Consumption among African Countries: Evidence from Sequential Panel Selection Method - Anoruo, Emmanuel; DiPietro, William R. (International Journal of Energy Economics and Policy, 2014)
This paper applies a battery of panel unit root procedures to test for convergence in per capita energy consumption among 22 African countries. Specifically, the study implements both the conventional panel unit root testing procedures and the Sequential Panel Selection Method (SPSM). The results from the standard panel unit root tests provide evidence of convergence in per capita energy consumption for the 22 countries as a group. However, these procedures lack the ability to separate the series in the panel into stationary and nonstationary groups. The results from the SPSM procedure provide support for per capita energy consumption convergence for Angola, Mozambique, Libya, Tanzania, Zambia, Ethiopia, Algeria, Senegal, Congo Republic, South Africa, Benin, Cameron, and Nigeria. For Tunisia, Cote d’Ivoire, Sudan, Gabon, Zimbabwe, Morocco and Togo, the results from the SPSM procedures suggest that their per capita energy consumption series have not converged with the other panel members. Keywords: Per capita energy consumption; SPSM; convergence; panel KSS unit root test JEL Classifications: C22; C23; Q41